For an ecology of scientific work: science, politics and the case of streams Pampa and Luiz Rau in Novo Hamburgo, Brazil - Meirelles,M. (2015)
If, like Weber writes, every knowledge is objective in terms of evolving the interests of researchers and the agencies, in this article, we investigate that, which has been researched about two streams: Pampa and Luiz Rau. In doing so, in addition to highlighting what has caught the researchers' attention, this paper manages to point out a few gaps and fruitful fields of study which extend beyond the hard sciences. This study is, therefore, characterized as an essay review paper that sets out to use anthropology of science to think about the limitations and advances the studies about the two streams have achieved, as well as their social impact.